2014
DOI: 10.1111/asj.12219
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vaginal discharge with the Metricheck device and the relationship to reproductive performance in postpartum dairy cows

Abstract: Vaginal mucus during estrus was examined with the Metricheck device and the relationship to the reproduction of high-yielding dairy cows was studied. The study was conducted in 99 dairy herds located in Western Germany and 1348 Holstein-Friesian heifers and cows showing spontaneous estrus were examined. Independent of the Metricheck result, the animals were inspected by professional insemination technicians and those suitable for insemination (n = 989) were bred by artificial insemination (AI). Reproductive pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This scoring system has been correlated with the presence of pathogenic bacteria and the prognostic value for pregnancy success . Postpartum cows with clear discharge (score 0) had higher non-return rate at 90 days (56%) than cows with abnormal vaginal secretion (score >1) (48% P< 0,05) (Lambertz et al, 2014). However, vaginal discharges are not always indicative of uterine infection because many cases of vaginitis or cervicitis can occur in parallel without uterine disorders and vice versa.…”
Section: Non-invasive Uterine Assessment Of Endometrial Receptivitymentioning
confidence: 99%
“…This scoring system has been correlated with the presence of pathogenic bacteria and the prognostic value for pregnancy success . Postpartum cows with clear discharge (score 0) had higher non-return rate at 90 days (56%) than cows with abnormal vaginal secretion (score >1) (48% P< 0,05) (Lambertz et al, 2014). However, vaginal discharges are not always indicative of uterine infection because many cases of vaginitis or cervicitis can occur in parallel without uterine disorders and vice versa.…”
Section: Non-invasive Uterine Assessment Of Endometrial Receptivitymentioning
confidence: 99%
“…Additionally, the character of vaginal discharge was assessed using the Metricheck (MC) device (Simcro Tech Ltd.;McDougall et al, 2007) on d 8 and 15 p.p. Vaginal discharge was scored on a 0 to 3 scale (score 0 = clear, mucoid discharge; score 1 = mucopurulent discharge with <50% of pus; score 2 = mucopurulent discharge with >50% of pus; score 3 = brownish-reddish, watery, foul-smelling discharge) as described previously (Sheldon and Dobson, 2004;Sheldon et al, 2006;McDougall et al, 2007;Senosy et al, 2012;Lambertz et al, 2014). Based on MC score and RBT on d 8 and 15 p.p., respectively, 4 uterine health categories (UHC) were defined (score 1 = MC score ≤1 and RBT <39.5°C; score 2 = MC score ≤1 and RBT ≥39.5°C; score 3 = MC score ≥2 and RBT <39.5°C; score 4 = MC score ≥2 and RBT ≥39.5°C).…”
Section: Clinical Examinations and Samplingmentioning
confidence: 99%
“…Day 2 was included as a covariate.3 In an ordinal regression model with a dichotomous predictor variable (CON vs. FM) and an ordinal dependent variable (e.g., MC score 0-3), the odds ratio describes the risk of finding a higher category of the dependent variable that comes with a one-unit increase in the predictor variable. For example, when FM is defined as reference category within the predictor variable, an odds ratio = 1.5 indicates a 1.5 times increased risk for CON cows to fall into a higher category of the dependent variable compared with FM.4 Metricheck score was assessed on a 0 to 3 scale modified according to previous recommendations(Sheldon and Dobson, 2004;Sheldon et al, 2006;McDougall et al, 2007;Senosy et al, 2012;Lambertz et al, 2014).5 Four different uterine health categories were defined by MC score and rectal body temperature (RBT; category 1 = MC score ≤1 and RBT <39.5°C; category 2 = MC score ≤1 and RBT ≥39.5°C; category 3 = MC score ≥2 and RBT <39.5°C; category 4 = MC score ≥2 and RBT ≥39.5°C).6 Rumen fill was recorded on a 1 to 5 scale according toZaaijer and Noordhuizen (2003).7 Locomotion score was recorded on a 1 to 5 scale according toSprecher et al (1997).…”
mentioning
confidence: 99%
“…Previous studies carried out on dairy cattle herds in North America (Bicalho et al, 2016; Ribeiro et al, 2013) and Europe (Canadas et al, 2020; Lambertz et al, 2014) reported reduced reproductive performance of cows affected by endometritis; however, in Brazil, to the best of our knowledge, there are no studies describing reproductive performance and risk factors of cows without uterine disease and cows affected by CE and SE between 28 and 33 days after calving.…”
Section: Introductionmentioning
confidence: 99%